ANALISIS KELAYAKAN USAHA PETERNAKAN BURUNG PUYUH PEDAGING (Coturnix coturnix japonica) DI KECAMATAN KERUMUTAN - Laila, Widya; Aprilia, Rita; Yunita, Imelda (Jurnal Teknik dan Teknologi Tepat Guna, 2025)
Quail farming business is one of the potential businesses as the population increases and public awareness of the need for daily animal protein sources that are easy to get at affordable prices compared to other poultry meat. The objectives of this study are to find out the feasibility of Mr. Agung Wibowo's quail farming business in Kerumutan District based on market and marketing aspects, technical aspects, environmental aspects and financial aspects. Data collection is carried out by means of field surveys, interviews, literature studies and documentation. The result of this research is that the quail farming business owned by Mr. Agung Wibowo in Kerumutan District is worthy of continuing. Based on market and marketing aspects, it is feasible because it has segmentation, clear targeting and market position, and a selling price that is quite competitive compared to other poultry meat prices and has a marketing strategy with a marketing mix. From the technical aspect, it is feasible because it has all the necessary facilities and equipment and have a clear production cycle and business location. From the environmental aspect, it is feasible because of the environmental impact management. Based on the results of the calculation, the financial aspect is declared feasible. Where the R/C Ratio value > out of 1, which is 1.5. The value of the π/C Ratio is 0.57% higher than the value of the BRI Simpedes savings interest rate of 0.25%. Production BEP Value < Production Amount and BEP Value Price < Selling Price per Head. From the results of the calculation of the Production BEP Value is 3,312 heads. So 3,312 Heads < 5,162 Heads and the result of calculating the BEP Price Value is Rp. 3,011. Then Rp. 3,011 < Rp. 5,500.